The use of near infrared reflectance spectroscopy (NIRS) for the chemical analysis of meat and feedstuffs - Viljoen, Mariaan (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MScAgric)--University of Stellenbosch, 2003.